2013
DOI: 10.1016/j.redox.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 activation supports cell survival during hypoxia and hypoxia/reoxygenation in cardiomyoblasts; the roles of reactive oxygen and nitrogen species

Abstract: Adaptive mechanisms involving upregulation of cytoprotective genes under the control of transcription factors such as Nrf2 exist to protect cells from permanent damage and dysfunction under stress conditions. Here we explore of the hypothesis that Nrf2 activation by reactive oxygen and nitrogen species modulates cytotoxicity during hypoxia (H) with and without reoxygenation (H/R) in H9C2 cardiomyoblasts. Using MnTBap as a cell permeable superoxide dismutase (SOD) mimetic and peroxynitrite scavenger and L-NAME … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 40 publications
4
36
0
Order By: Relevance
“…Activation of the Nrf2‐ARE signaling pathway is known to protect against oxidative stress‐induced cell death . Given the association of ASA with Nrf2‐ARE pathway, we explored the ASA dependent role of Nrf2‐ARE antioxidation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Nrf2‐ARE signaling pathway is known to protect against oxidative stress‐induced cell death . Given the association of ASA with Nrf2‐ARE pathway, we explored the ASA dependent role of Nrf2‐ARE antioxidation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…# Significant differences from the treatment with A/R alone (P < 0.05). 21,39 Under normal conditions, Nrf2 is located in the cytoplasm and binds with Keap1. 36 This important enzyme has been shown to reduce I/R-induced myocardial damage.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of a variety of endogenous inflammatory cytokines and proinflammatory proteins, including NO, leukotrienes, iNOS and TNF-α, result in myocardial dysfunction [40]. Kolamunne et al [41] showed that L -NAME has a cell-protective role only in the hypoxic state. Furthermore, a high concentration of exogenous NO opens mPTPs, resulting in apoptosis [42].…”
Section: Discussionmentioning
confidence: 99%